UKRAINE’S PATH TO INCLUSIVITY: THE ROLE OF PUBLIC COUNCILS IN GOVERNANCE - Ivanenko, NataliyaPetrovna; Oleksandr, Mykolaiovych Voronin; Oksana , Yuriyivna Kovalenko (Top Journal of Public Policy and Administration (TJPPA), 2023)
This study examines the relationship between individuals and subjects of public administration in the context of modernisation of Ukrainian society and the state. The aim of this study is to identify the possibilities of introducing civilised aspects of relations between subjects of state power and civil society into management activities. The paper employs analytical substantiation of the problems under study, focus group, expert survey, and research-to-practice developments in the problems of relations between public councils and subjects of public administration. The authors conclude that public councils as a temporary consultative and advisory body formed under the executive authority to promote public participation in the development and implementation of national policy are an integral component of a democratic society. The practical aspect of this problem can serve as a certain example for other countries, especially for the former republics of the USSR. This study hypothesises that public councils can play a positive role in making important decisions by local self-government bodies at the level of regional public administration. The study employed sources such as the Constitution of Ukraine and Resolutions of the Cabinet of Ministers of Ukraine "On the Public Council" and "On Ensuring Public Participation in the Development and Implementation of National Policy."